ADVANTAGES OF USING INTEGRATIVE-COGNITIVE TASKS IN DEVELOPING PROFESSIONAL COMPETENCE IN FUTURE PRIMARY CLASS TEACHERS - Karimova Kamola Kamilkizi (Web of Journals Publishing, 2024)
The high potential of the teaching staff directly serves as the basis for the perfect organization of the educational process. After all, the more competencies a teacher has developed, the better results he can achieve in his pedagogical activities. Among them, professional competence is the most necessary set of skills and qualifications for a teacher. This article presents several recommendations for the formation of such professional competences for future primary school teachers and, at the same time, to achieve their high level of improvement.
Keywords: professional competence, pedagogical activity, integration, integrative activity, cognitive activity, integrative-cognitive task, educational process, knowledge, skill.